Enhancing Student Learning Outcomes in PAI Subjects: The Impact of PowerPoint Learning Media Application - Umar Manshur; Tamimi Insanul Jamil; Saif Fakhruddin Sanusi (Educazione: Journal of Education and Learning, 2024)
This study investigates the impact of PowerPoint-based learning media on student learning outcomes in Islamic Religious Education (PAI) subjects. Given the growing reliance on technology in education, this research aims to assess whether PowerPoint media can enhance student understanding and academic performance in a traditional classroom setting. The research utilizes an experimental design with a pretest-posttest control group. A total of 20 grade IX students from SMPN Lumajang participated, with 10 in the experimental group using PowerPoint-based media and 10 in the control group receiving conventional lecture-based instruction. Data were collected through pretest and post-test assessments, and the effectiveness of the media was analyzed using paired sample t-tests. Results reveal that the experimental group showed a significant improvement in learning outcomes, with a mean post-test score of 87 compared to 71 in the control group (p < 0.05). The study concludes that PowerPoint-based learning media significantly enhances student learning outcomes in PAI subjects, suggesting its potential for broader application in religious education. These findings provide empirical evidence of technology’s role in improving educational effectiveness and offer practical implications for integrating multimedia tools into teaching strategies.